Knowledge, Power, and Social Policy: John M. MacEachran and Alberta’s 1928 Sexual Sterilization Act - Puplampu, Korbla P. (Alberta Journal of Educational Research, 2008)
This article examines how academic knowledge and power have shaped the discourse on human classification and how political authorities use academic knowledge producers to legitimize public policy. Specifically, the article draws on the role of John M. MacEachran, a former academic at the University of Alberta, in the implementation of the Alberta 1928 Sexual Sterilization Act. The article argues that political authorities use academics and their knowledge in social policy when there is consistency with the interests of broader sociopolitical forces. Drawing on critical pedagogy, the selective use of academic knowledge-producers and the implications are discussed with reference to the relationship between educators and learners and university-society relations in general.